2022
DOI: 10.7717/peerj.12790
|View full text |Cite
|
Sign up to set email alerts
|

Sixteenth-century tomatoes in Europe: who saw them, what they looked like, and where they came from

Abstract: Background Soon after the Spanish conquest of the Americas, the first tomatoes were presented as curiosities to the European elite and drew the attention of sixteenth-century Italian naturalists. Despite of their scientific interest in this New World crop, most Renaissance botanists did not specify where these ‘golden apples’ or ‘pomi d’oro’ came from. The debate on the first European tomatoes and their origin is often hindered by erroneous dating, botanical misidentifications and inaccessible h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…It has been suggested that these old tomato cultivars could help to revive ancient resistance to pests and diseases, and thus contribute to the development of new cultivars with the 'original' taste. In their review, Andel et al [ 96 ] screened early 16th century tomatoes mentioned in descriptions or visible herbarium specimens, including the ‘En Tibi’ herbarium, to show that different landraces of tomatoes were introduced to Europe from Mesoamerica very soon after its discovery. They noticed great variety in flower and fruit shapes, sizes, and colors, indicating that the earliest tomatoes in Europe came in a much wider variety of than had previously been thought.…”
Section: Tomatoesmentioning
confidence: 99%
“…It has been suggested that these old tomato cultivars could help to revive ancient resistance to pests and diseases, and thus contribute to the development of new cultivars with the 'original' taste. In their review, Andel et al [ 96 ] screened early 16th century tomatoes mentioned in descriptions or visible herbarium specimens, including the ‘En Tibi’ herbarium, to show that different landraces of tomatoes were introduced to Europe from Mesoamerica very soon after its discovery. They noticed great variety in flower and fruit shapes, sizes, and colors, indicating that the earliest tomatoes in Europe came in a much wider variety of than had previously been thought.…”
Section: Tomatoesmentioning
confidence: 99%
“…Manioc, mentioned by several voyagers including the same Columbus in his first voyage, and Pedro Alvares Cabral when traveling to Brazil, even if mistaken by yam, or inhame [24]. Tomato, a product that soon appeared in the gardens of Italian aristocrats, was later studied by Renaissance naturalists, even if the specific geographical origin is not clear [25]. Another crop, the potato, was first observed in 1551 by Pedro de Valdivia, reported by López de Gómara in 1552, and then, documented from the Canary island in 1567 [26].…”
Section: The First Voyagers Through the New World And The Impact Of T...mentioning
confidence: 99%
“…Centrant-se específicament en la tomaca, les informacions més antigues indiquen que, després de l'entrada de les primeres llavors pel port de Sevilla en el segle XVI, l'espècie va viatjar a Itàlia, on va captivar l'atenció dels botànics del Renaixement. Posterior a aquesta introducció, la tomaca va proliferar per tota la regió mediterrània i els països del sud d'Europa en els segles següents (van Andel T., et. al.…”
Section: Introduccióunclassified